Shock Response Spectra Reconstruction of Pointwise Explosive-Induced Pyroshock Based on Signal Processing of Laser Shocks - S. Y. Chong; J. R. Lee; C. W. Kong (Shock and Vibration)
Pyroshock has been an issue of great concern for aerospace and defense industrial applications. When pyroshock devices are detonated, they can easily cause failures in electronic, optical, relay, and magnetic components generally in mid- and far-fields which is not avoidable at the design level. Thus, many numerical and experimental pyroshock simulations have been widely studied to predict explosive-induced pyroshock effect quantitatively, especially the shock response spectrum (SRS). In this study, a laser shock-based pyroshock reconstruction method is proposed to simulate a pointwise explosive-induced pyroshock signal. The signal processing algorithm for the laser shock-based pyroshock reconstruction is developed in a LabVIEW platform and consists of subbands decomposition, SRS matching in decomposed bands, and wave synthesizing. Then, two experimental setups are configured to obtain pyroshock signals and laser shock signals at four points in an aluminum plate. The reconstructed pyroshock signals synthesized according to the signal processing of the laser shocks demonstrate high similarity to the real pyroshock signals, where the similarity is evaluated by the mean acceleration difference between the SRS curves. The optimized settings of the subband decomposition were obtained and can be in the future used in a pyroshock simulator based on laser shock for pyroshock simulation at any arbitrary point.